2019
DOI: 10.1029/2019jf005005
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Coarse Organic Matter and Depositional Environment to Carbon Burial Behind Dams in Mountainous Environments

Abstract: The relationship between carbon burial and sedimentation in reservoirs is unknown, contributing to uncertainty in our understanding of the net impact of dams to the global carbon budget and exposing gaps in our fundamental understanding of the transport, processing, and deposition of organic matter in fluvial and lacustrine systems. Taking opportunistic advantage of the removal of two high‐head dams, we investigate this relationship by developing a stratigraphic, process‐based framework to estimate total carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…However, our study adds an important novel comparison between the relative magnitude of spatial and temporal heterogeneity, a central question in the study of reservoirs (Thornton et al 1990). Similar to our findings, many studies have documented that spatial heterogeneity of biogeochemistry is substantial, and also highly variable over time (Gloss et al 1980;Shaughnessy et al 2019;Borges et al 2008;Soares et al 2012;Stratton et al 2019;Linkhorst et al 2020).…”
Section: Implications Of Time As a Dominant Axis Of Heterogeneitysupporting
confidence: 91%
See 1 more Smart Citation
“…However, our study adds an important novel comparison between the relative magnitude of spatial and temporal heterogeneity, a central question in the study of reservoirs (Thornton et al 1990). Similar to our findings, many studies have documented that spatial heterogeneity of biogeochemistry is substantial, and also highly variable over time (Gloss et al 1980;Shaughnessy et al 2019;Borges et al 2008;Soares et al 2012;Stratton et al 2019;Linkhorst et al 2020).…”
Section: Implications Of Time As a Dominant Axis Of Heterogeneitysupporting
confidence: 91%
“…Of freshwater ecosystems, reservoirs in particular play a disproportionately large role in global biogeochemical cycles, transforming and burying large amounts of carbon (C), nitrogen (N), and phosphorus (P) (Harrison et al 2009;Maavara et al 2015Maavara et al , 2020Powers et al 2015;Shaughnessy et al 2019;Stratton et al 2019). Reservoirs receive a much higher quantity of nutrients (N, P) and organic C than many naturally formed lakes due to their high watershed-to-surface area ratio and corresponding large terrestrial drainage area, making them important for biogeochemical processing within the landscape (Thornton et al 1990;Harrison et al 2009;Hayes et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, if compared to other hydroelectric reservoirs at low latitudes, our conclusion remains that OC burial in CUN is high. Importantly, comparisons of the average SAR and OC burial rate between studies may be complicated by different sampling schemes, as sedimentation can vary in space and time (Radbourne et al, 2017;Stratton et al, 2019); for example, while in some studies, sites along the margins with zero sedimentation were sampled (e.g., Mendonça et al, 2014; our study), in other studies this was not sampled (Moreira-Turcq et al, 2004;Knoll et al, 2014). G. R. Quadra et al: C burial and CH 4 pore water in the sediments of an Amazonian hydroelectric reservoir…”
Section: Sar and Oc Burial In An Amazonian Reservoirmentioning
confidence: 84%
“…The freshwater OC burial rate varies both in space and time due to many factors, such as land cover, hydrological conditions, OC and nutrient input, and climate change (Radbourne et al, 2017;Stratton et al, 2019). Several studies have shown that reservoirs bury more OC per unit area than lakes, rivers and oceans (Mulholland and Elwood, 1982;Mendonça et al, 2017), which may be attributed to the high sedimentation rate caused by the extensive sediment trapping when water flow is dammed (Vörösmarty et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a detailed 85‐year sedimentary record from a reservoir on the Elwha River, which drains alpine wilderness in northwestern Washington, was recently exposed after permanent lake drainage and dam removal (Ritchie et al, 2018). Those >50‐m‐thick strata (which accumulated at ~60 cm/year) have been examined to resolve facies architecture (Stratton et al, 2019; Stratton & Grant, 2019) but do not yet have a chronology established to evaluate temporal sedimentation history or to correlate those changes with the >100‐year hydrograph recorded just downstream. Future studies could pursue this and other lacustrine records to evaluate whether basin sediment yields have increased during the modern warming era.…”
Section: Observed Changes To Sedimentary and Geomorphic Processes: An...mentioning
confidence: 99%